Studi Komparatif Penerapan Voluntary Disclosure Program Di Indonesia, Malaysia, Dan Singapura - Muhammad Syahfatras Vientino; Muhammad Ridhwan Galela (JURNAL PAJAK INDONESIA, 2022)
An increase in state budget revenues is necessary to streamline the development program and one way is to expand the existing tax base by creating a Voluntary Disclosure Program (VDP/PPS). There are no specific guidelines regarding the mechanism for implementing PPS for each country, so each country has a different mechanism. This study aims to determine the different mechanisms of the implementation of PPS in Indonesia, Malaysia, and Singapore, as well as to provide recommendations for the implementation of PPS in Indonesia. This study uses data collection techniques in the form of library research with non-probability sampling using the purposive sampling method. The results obtained show differences in the implementation mechanism in the three countries in terms of the type of tax coverage, period, participant criteria, amnesty rates, and basis of disclosure.